Long-Term Safety and Efficacy of Blonanserin Transdermal Patches in Japanese Patients with Schizophrenia: A 52-Week Open-Label, Multicenter Study - Iwata, Nakao (CNS Drugs, 2019)
BACKGROUND: Blonanserin transdermal patch therapy is now available in Japan for the treatment of schizophrenia and may provide several advantages over the tablet formulation. OBJECTIVE: The aim was to evaluate the long-term safety and efficacy of blonanserin transdermal patches in Japanese patients with schizophrenia. METHODS: An open-label study was conducted in adults with schizophrenia at 37 sites in Japan. Patients were enrolled in either cohort 1 or 2. Patients in cohort 1 received 8–16 mg/day blonanserin tablets for 6 weeks and then 40–80 mg/day blonanserin patches for 52 weeks. The dose of blonanserin patches was determined according to the dose of the tablets. In cohort 2, every patient started from 40 mg/day and then 40–80 mg/day blonanserin transdermal patches for 52 weeks. Both cohorts had 1–2 weeks of follow-up. Safety endpoints included the incidence of adverse events (AEs), treatment-related AEs, extrapyramidal AEs [also assessed using the change in Drug-Induced Extrapyramidal Symptoms Scale (DIEPSS) score], the use of any concomitant antiparkinsonian drugs, and skin-related AEs, including skin irritation. Patients also underwent assessment of laboratory values including for serum prolactin concentration, vital signs, body weight, electrocardiographic (ECG) changes, and the corrected QT (QTc) interval. Suicidal ideation was assessed via the Columbia-Suicide Severity Rating Scale (C-SSRS) score. Efficacy was assessed via duration of blonanserin transdermal patch treatment, Positive and Negative Syndrome Scale (PANSS) total and subscale scores, and Clinical Global Impression-Severity (CGI-S) scores. Other endpoints included total Drug Attitude Inventory 10 (DAI-10) scores, EuroQol-5 Dimension (EQ-5D) effect values, and a patient questionnaire about the dosage form. RESULTS: A total of 223 patients with consents, 117 in cohort 1 and 106 in cohort 2 were included in the study. Of the 117 patients in cohort 1, 108 were treated with blonanserin tablets, and 97 received blonanserin patches and were included in the safety analysis set. In cohort 2, 103 of the 106 patients were treated with blonanserin transdermal patches and were included in the safety analysis set. In total, 91 patients were male (45.5%). The mean age was 43.8 years. Discontinuation occurred in 40 patients (41.2%) in cohort 1 and 44 patients (42.7%) in cohort 2. Discontinuation resulted from AEs in 18.6% (cohort 1) and 11.7% (cohort 2) and from withdrawal of consent in 13.4% (cohort 1) and 20.4% (cohort 2), and seven patients overall discontinued due to skin reactions. AEs were reported in 174 patients (87.0%), and 13 serious AEs occurred in 12 patients (6.0%), of which six patients were in cohort 1 and six patients were in cohort 2. Serious AEs were six schizophrenia (n = 6) and seven other AEs (n = 6), which included impulse-control disorder, fracture, epistaxis, asthma, pneumonia aspiration, pneumonia hemophilus, and pneumonia. The most common AEs were nasopharyngitis (n = 62, 31.0%), application site erythema (n = 45, 22.5%), application site pruritus (n = 23, 11.5%), and akathisia (n = 20, 10.0%). AE incidence was similar in cohort 1 (84.5%) and cohort 2 (89.3%). Extrapyramidal and skin-related AEs were reported in 51 patients (25.5%) and 83 patients (41.5%), respectively. None of these AEs were serious. The mean change from baseline in total DIEPSS score at Week 52 {last observation carried forward [LOCF] (standard deviation [SD])} was −0.1 (1.55), indicating no marked effect. In terms of concomitant medications used in cohort 1 and cohort 2, 33.0% (32/97) and 22.3% (23/103) used antiparkinsonian drugs, respectively. The majority of skin-related AEs occurred early in treatment and were appropriately managed with topical therapies. Of the patients who answered “No” to all C-SSRS categories at baseline (n = 129), 13 patients (10.1%) were evaluated as having emergence of suicidal ideation. Among patients who answered “No” to all C-SSRS suicidal behavior categories at baseline (n = 172), one (0.6%) was evaluated as having suicidal behavior during blonanserin transdermal patch treatment. There were no clinically significant changes in laboratory tests or examinations, including prolactin level, vital signs, body weight, ECG, metabolism-related parameters, and QTc interval. The mean (SD) change in body weight was − 0.04 (4.561) kg and − 0.67 (6.841) kg in cohort 1 and cohort 2, respectively. The mean changes from baseline in PANSS total score at Week 52 (LOCF [SD]) were − 0.1 [11.6] and − 3.4 [15.3] in cohort 1 and 2, respectively. PANSS scores did not change after switching from tablet to patch formulation in cohort 1 and decreased over the 52 weeks of treatment with the blonanserin patches. The mean change from baseline in CGI-S score at Week 52 (LOCF [SD]) was − 0.2 [1.03] in both cohorts combined. After 52 weeks of blonanserin patch treatment, the total DAI-10 score increased or remained unchanged compared with baseline in 82 of the 129 patients (63.6%) for whom these data were available. In the intention-to-treat population of the combined cohorts (n = 200), the mean (SD) change from baseline in EQ-5D score at the last assessment was − 0.0365 (0.17603). Patients’ attitudes to the blonanserin transdermal patches were generally positive. CONCLUSIONS: Blonanserin transdermal patches are safe and effective in the long-term treatment of schizophrenia. CLINICALTRIALS.GOV REGISTRATION: NCT02335658. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40263-019-00692-6) contains supplementary material, which is available to authorized users.